Herbal combination from Moringa oleifera Lam. and Curcuma longa L. as SARS-CoV-2 antiviral via dual inhibitor pathway: A viroinformatics approach. - Viol Dhea Kharisma; Aggy Agatha; Arif Nur Muhammad Ansori; Muhammad Hermawan Widyananda; Wahyu Choirur Rizky; Tim Godefridus Antonius Ding; Marina Derkho; Irina Lykasova; Yulanda Antonius; Imam Rosadi; Rahadian Zainul (GarVal Editorial Ltda., 2022)
Context: The COVID-19 outbreak is caused by the transmission and infection of SARS-CoV-2 at the end of 2019. It has led many countries to implement lockdown policies to prevent the viral spreading. Problems arise in a COVID-19 patient because of viral infection that leads to a systemic response in the immune system, specifically due to cytokine storm. Moreover, the antiviral drugs that have not been found. Indonesia had a variety of traditional medicines, such as is 'jamu'. It consists of a mixture of natural ingredients such as Moringa oleifera Lam. and Curcuma longa L. Aims: To identify the activity of dual inhibitors as antiviral and anti-inflammatory agents from herbal combination compounds. Methods: Sample was collected from PubChem (NCBI, USA) and Protein Data Bank (PDB), then drug-likeness analysis using Lipinski rule of five in SCFBIO web server and bioactive probability analysis of bioactive compounds were conducted by PASS web server. Furthermore, the blind docking method was performed using PyRx 0.8 software to determine the binding activity and molecular interaction by PoseView web server and PyMol software v2.4.1 (Schrödinger, Inc, USA). Results: Cryptochlorogenic acid and curcumin have been computationally proven as dual inhibitors for antivirals by inhibiting Mpro SARS-CoV-2 and as anti-inflammatory through inhibition of NFKB1 activity. However, the results are merely computational so that it must be validated through a wet lab research. Conclusions: The combination of Moringa oleifera Lam. and Curcuma longa L. is predicted to have antiviral and anti-inflammatory activity through dual inhibitor mechanism played by cryptochlorogenic acid and curcumin.